KEWENANGAN PENGADILAN NIAGA DALAM PENYELESAIAN PERKARA PERNIAGAAN LAIN BERDASARKAN UNDANG-UNDANG NOMOR 37 TAHUN 2004 - Tata Wijayanta (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2008)
The research is a qualitative research. The data which is used are primary and secondary data from library and field research. The research aims to analyze the authority of the commercial court to examine and settle commercial case. The definition and means of the other commercial case which have been examined and settled by the commercial court. The result of research shows that the commercial court has carried out the authority since 2001. Besides, commercial cases include trade mark case, patents, copy right and industrial designs. From 2001 up to 2006, four hundreds and seven (407) cases have been examined and settled by the court. The most are trade mark disputes, with two  hundreds and seventy two (272) disputes (91,4%).